THE EDUCATIONAL ENVIRONMENT OF THE NATIONAL AVIATION UNIVERSITY AS A FACTOR FOR THE FORMATION OF ACADEMIC STUDENT MOBILITY - Скирда, Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article describes the algorithm for the construction of the educational environment of the National Aviation University (NAU) as a forming factor in the academic mobility of students. It has been found out that the algorithm has the following logic: presentation of the mission and vision, providing information about the university, its scientific activity, measures for ensuring the quality of education, up-to-date information for students and university applicants; the formation of the university news, including coverage of developments in academic mobility; description of the content of the academic mobility event, photo report; the formation of an archive of events that took place in the university on a specific topic. Seven consecutive stages of formation of NAU’s educational environment have been identified and characterized in the context of solving the problems of formation of academic mobility of students: the first stage is determining the purpose of NAU’s activity and strategic priorities of its development, taking into account the objective global tendencies of higher education development, in general, and aviation, in particular; the second stage is the identification of the priority idea of ​​the university development; the third stage is the determination of values, key principles and scientific approaches to the organization of the university’s activity; the fourth stage - development of directions of achievement of the purpose and strategic priorities of development of the university; the fifth stage - determining the magnitude of transformations; the sixth stage - formation of readiness of the management apparatus and the tutor staff of NAU to form the academic mobility of students; the seventh stage - achievement and evaluation of the result - qualitative changes in the system of formation of academic mobility of students in the educational process of NAU. A model of the NAU’s educational environment was developed as a factor in shaping the academic mobility of students, the educational portal of the university where you can get acquainted with the strategic and conceptual documents of measures for the internationalization of the development of NAU, in particular internationalization, international relations and strategic partnership activities (eg: trainings, seminars, conferences on academic mobility, internships, etc.); educational process, which involves the formation of students’ readiness for academic mobility through mastering the content of academic disciplines. Keywords: academic mobility; higher education; educational environment